Redeployment of Orthopaedic Advanced Practice Providers at Academic Medical Centers During the COVID-19 Pandemic. (July 2020) - Kidd, Vasco Deon
Abstract : The novel coronavirus (SARS-CoV-2) represents a rapidly evolving pandemic. Health systems are scrambling to mobilize and redeploy their medical staff in the fight against COVID-19. Orthopaedic nurse practitioners/physician assistants should be part of any redeployment strategy to address unmet needs during these unprecedented times. This article discusses redeployment considerations and strategies that utilize these providers appropriately while mitigating risks.